Borrelia burgdorferi: Carbon Metabolism and the Tick-Mammal Enzootic Cycle - Corona, Arianna (Microbiol Spectr, 2015)
Borrelia burgdorferi, the spirochetal agent of Lyme disease is a zoonotic pathogen that is maintained in a natural cycle that typically involves mammalian reservoir hosts and a tick vector of the Ixodes species. During each stage of the enzootic cycle B. burgdorferi is exposed to environments that differ in temperature, pH, small molecules, and most importantly, nutrient sources. B. burgdorferi has a highly restricted metabolic capacity as it does not contain a tricarboxylic acid cycle, oxidative phosphorylation or any pathways for de novo biosynthesis of carbohydrates, amino acids or lipids. Thus, B. burgdorferi relies solely on glycolysis for ATP production and is completely dependent on the transport of nutrients and cofactors from extracellular sources. Herein, pathways for carbohydrate uptake and utilization in B. burgdorferi are described. Regulation of these pathways during the different phases of the enzootic cycle is discussed. In addition, a model for differential control of nutrient flux through the glycolytic pathway as the spirochete transits through the enzootic cycle is presented.